Association of Proximal Tubular Secretory Clearance with Long-Term Decline in Cognitive Function. Issue 7 (July 2022) - Lidgard, Benjamin; Bansal, Nisha; Zelnick, Leila R.; Hoofnagle, Andrew; Chen, Jing; Colaizzo, Derek; Dobre, Mirela; Mills, Katherine T.; Porter, Anna C.; Rosas, Sylvia E.; Sarnak, Mark J.; Seliger, Stephen; et al.
Significance Statement: Patients with CKD are at high risk for cognitive impairment and progressive cognitive decline. The retention of organic solutes, which are predominantly cleared by tubular secretion, is hypothesized to contribute to cognitive impairment in such patients. In a multicenter prospective study of 2326 participants with CKD who were initially free of cognitive impairment, the authors found that lower 24-hour kidney clearance of a panel of secretory solutes was associated with cognitive decline, independent of eGFR and proteinuria. These findings highlight the potential contribution of kidney tubular clearance of secretory solutes to maintain normal cognitive function. Further work is needed to determine the mechanisms underpinning the associations between lower secretory clearance and cognitive decline. Visual Abstract: Abstract : Background: People with chronic kidney disease (CKD) are at high risk for cognitive impairment and progressive cognitive decline. Retention of protein-bound organic solutes that are normally removed by tubular secretion is hypothesized to contribute to cognitive impairment in CKD. Methods: We followed 2362 participants who were initially free of cognitive impairment and stroke in the prospective Chronic Renal Insufficiency Cohort (CRIC) Study. We estimated tubular secretory clearance by the 24-hour kidney clearances of eight endogenous solutes that are primarily eliminated by tubular secretion. CRIC study investigators assessed participants' cognitive function annually using the Modified Mini-Mental State (3MS) Examination. Cognitive decline was defined as a sustained decrease of more than five points in the 3MS score from baseline. Using Cox regression models adjusted for potential confounders, we analyzed associations between secretory solute clearances, serum solute concentrations, and cognitive decline. Results: The median number of follow-up 3MS examinations was six per participant. There were 247 incident cognitive decline events over a median of 9.1 years of follow-up. Lower kidney clearances of five of the eight secretory solutes (cinnamoylglycine, isovalerylglycine, kynurenic acid, pyridoxic acid, and tiglylglycine) were associated with cognitive decline after adjustment for baseline eGFR, proteinuria, and other confounding variables. Effect sizes ranged from a 17% to a 34% higher risk of cognitive decline per 50% lower clearance. In contrast, serum concentrations of the solutes were not associated with cognitive decline. Conclusions: Lower kidney clearances of secreted solutes are associated with incident global cognitive decline in a prospective study of CKD, independent of eGFR. Further work is needed to determine the domains of cognition most affected by decreased secretory clearance and the mechanisms of these associations.